Generación y evaluación de nitrógeno bien expresado a partir de la asociación simbiótica Azolla-Anabaena para producción de brócoli (Brassica oleracea L.) en la quinta experimental “La Argelia” - Abad Calva, Gabriela Natali (2022)
Nitrogen is an element present in the atmosphere at 78%, however, the quantities available in the soil are not sufficient for plant nutrition. Several years ago, the human learned to synthesize and manufacture inorganic nitrogen fertilizers so as to supply the nutrient deficiency in the soil, currently the dependence on this macronutrient threatens food security due to its runaway prices. Therefore, safe and sustainable alternatives are sought to meet the needs of the agricultural sector. The implementation of Azolla, an aquatic fern, capable of setting nitrogen through symbiosis with the Anabaena cyanobacterium, may be the solution to enrich the soil with macronutrients and micronutrients. In the present research, Azolla was applied as a natural source of nitrogen for the production of broccoli crops, in the Sucre parish on the properties of the experimental farm "La Argelia" of the Universidad Nacional de Loja. Five treatments were established: Testigo (25 kg soil), Urea (25 kg soil + 40 mgl-1 N), NitrAgua (25 kg soil + 100 mgl-1 N), Azolla (18 kg soil + 8.33 kg of Azolla) and Azolla plus NitrAgua (Azolla 18 kg of soil + 8.33 kg of Azolla + 100 mgl-1 N).The data gathered was: plant height, number of leaves, stem diameter and pella weight at 15, 30, 60, and 75 days. Obtaining the best results at the 75 days, providing Azolla biomass plus NitrAgua, in plant height (70 cm), stem diameter (19 mm), number of leaves (21), and, pella weight (305 g). To sum up, the use of Azolla biomass plus the application of NitrAgua is an effective biofertilizer owing to the fact that the broccoli crop benefits from the well-expressed nitrogen supply. Keywords: Biofertilizer, Fixation, Nitrogen, Azolla, NitrAgua (Nbe), Azollario